A Brief Overview of SiC MOSFET Failure Modes and Design Reliability - Nel, Barry; Perinpanayagam, Suresh (Elsevier, 2017)
This paper briefly introduces various aspects which should be considered when implementing Silicon Carbide (SiC) based metal-oxide-semiconductor-field-effect-transistors (MOSFETs) into a design. There is an increasing trend regarding the use of these devices in various applications due to their improved performance over conventional Silicon (Si) based devices. The failure modes of SiC MOSFETs are discussed, as well as the indicators which signal device degradation and failure. The impact of packing design on reliability and performance is also discussed along with a number of application related concepts which bring to light some of the issues regarding the use of SiC MOSFETs as a relatively young technology.
Keywords: SiC; MOSFET; Overview; Reliability; Failure; Application